Development of assembly system with quick and low-cost installation. (17th April 2020) - Tennomi, Masanari; Okamura, Atsushi; Nakamura, Yuta; Abe, Taiki; Wakamatsu, Seiji; Tajima, Sho; Nishimura, Toshihiro; Hirai, Yuji; Sawada, Takuro; Ichikawa, Naoki; Tsuji, Tokuo; Yamazaki, Kimitoshi; et al.
ABSTRACT: Cell production systems for assembly operations generally require tool changes using several hands and a customized work table. The initial setting and resetting of the assembly system are costly. We implemented a system comprising the use of only two hands and without the requirement of tool changers. In addition, multiple sensors are used to perform tasks robustly to avoid errors. The peg-in-hole task is performed robustly against errors without the precise positioning of objects. The objective is to develop a system that is lean and agile and can be set up quickly. We evaluate this system based on the task-board and assembly tasks during the assembly challenge in the industrial robotics category of the World Robot Summit 2018. GRAPHICAL ABSTRACT: